Anticoagulation after VA-ECMO decannulation, providing new insights. (26th April 2021) - Maestro-Benedicto, A; Duran-Cambra, A; Vila-Perales, M; Sans-Rosello, J; Carreras-Mora, J; Vidal-Burdeus, M; Bragagnini, W; Tauron-Ferrer, M; Rossello, E; Koller-Bernhard, T; Cegarra, V; Pastor-Del Amo, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Venoarterial extracorporeal membrane oxygenation (VA-ECMO) is an essential tool for the management of refractory cardiogenic shock. Little is known about the incidence of thromboembolic events after V-A ECMO decannulation, although some studies report a high incidence of cannula-related venous thrombosis after venovenous extracorporeal membrane oxygenation (VV-ECMO). Due to this fact, in our institution anticoagulation therapy is systematically prescribed for at least 3 months after VA-ECMO per protocol.  AIM: The main objective of this study was to explore the feasibility of 3-month anticoagulation therapy after VA-ECMO decannulation. METHODS: We performed a prospective study that included 27 consecutive patients who were successfully treated with VA-ECMO in a medical ICU between 2016 and 2019 and were prescribed 3-month anticoagulation therapy per protocol after decannulation. Exclusion criteria was dying on ECMO or while on the ICU. Data analysis included demographics, mean days on ECMO, 3-month survival, and thromboembolic and bleeding events (excluding immediate post-decannulation bleeding, since anticoagulation was prescribed 24h after). RESULTS: Our cohort consisted mainly of men (N = 21, 78%), with a mean age of 60 ± 11 years and a mean time on VA-ECMO of 8 ± 3 days, who primarily suffered from post-cardiotomy cardiogenic shock (N = 9, 34%) or acute myocardial infarction (N = 6, 23%). 5 patients (18%) received a heart transplant. Regarding anticoagulation, 15 patients (60%) had other indications apart from the protocol, like incidental thrombus diagnosis (N = 7, 26%) or valve surgery (N = 5, 18%). Anticoagulation therapy was not feasible in 1 patient (4%) with severe thrombopenia. No patients had severe or life-threatening bleeding events in the follow-up, although 8 patients (30%) had bleeding events, mainly gastrointestinal bleeding (N = 4, 15%), requiring withdrawal of anticoagulation in 1 patient. The incidence of thromboembolic events was 7%; two patients with low-risk pulmonary embolisms. During the 3-month follow-up survival rate was 95%. CONCLUSIONS: This is the only study to date addressing the strategy of 3-month anticoagulation therapy after VAECMO, showing it is feasible and safe and may be helpful in reducing or ameliorate thromboembolic complications in the follow-up, although it is not exempt of complications.